IMPLEMENTASI PERATURAN DAERAH KABUPATEN KUDUS NOMOR 2 TAHUN 2010 TENTANG WAJIB BELAJAR 12 (DUA BELAS) TAHUN DI KABUPATEN KUDUS - Dewi Ratnawati; Sri Suwitri; Aloysius Rengga (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Education is very important because it is the primary means in an effort to improve the quality of human resources. In order to improve the quality of Kudus human resources in order to be more competitive, Kudus government regency has launched a Compulsory Education 12 year program. Compulsory Education 12 year program in Kudus Regency organized with the aim to provide quality and affordable education to the community. Implementation of the Compulsory Education 12 year program is regulated in the Regional Policy Kudus Regency Number 2 Year 2010. This study aims to determine how the implementation of the Compulsory Education 12 year program in Kudus Regency and find out the factors that support or hinder the implementation so as to know what needs to be repaired and maintained.This study uses a descriptive qualitative research method, to explain phenomena that affect the implementation of the Compulsory Education 12 year program in Kudus, guided by Regional Policy Kudus Regency No. 2 of 2010 about Compulsory Education 12 (Twelve) years. The data was collected by means of structured interviews with informants and documentation obtained from actual documents relating to the object of research. Analysis data in this qualitative study with data reduction, data presentation, and verification. From the research, found the phenomena that may affect the implementation of compulsory education 12 year program in Kudus, namely communication, environmental conditions, characteristics of the implementing agencies, and resources. It can be concluded that the implementation of the Compulsory Education 12 year program in Kudus Regency factors still exist that hinder implementation. This is because the human and financial resources to support the sustainability of the program has not been available for optimum.